Relationship of Language Learning Anxiety with Teacher and Peer Support - Tsehay, Alelign Abera; Kahsay, Mulugeta Teka (Bahir Dar Journal of Education, 2021)
The major objective of this study was to examine the relationship between English language learning anxiety and support (from teachers and peers) for Grade 9 students in rural-based secondary school. A questionnaire consisting of three different scales (Foreign Language Classroom Anxiety Scale [FLCAS], Teacher Support Scale and Peer Support Scale) was administered to 150 students (91 Female and 56 Male) selected from a population of 783 students through a stratified random sampling technique. Both descriptive statistics (frequency counts, means and standard deviations), and inferential statistics (Pearson Product Moment Correlation, and Fisher’s Z transform) were applied to analyze the data. The results of the study revealed that majority of the students were found to be moderately anxious in all dimensions of the anxiety scale. However, fear of negative evaluation was identified as the most anxiety provoking source for the participants. Moreover, the participants rated the support they got from their peers and teachers favourably well. All anxiety sub-variables (i.e. communication apprehension, fear of negative evaluation, test anxiety, and general English classroom anxiety) had a significant negative relationship with teacher support and peer support, with the exception of test anxiety with peer support. The correlation coefficients also showed notable differences in the strength of relationship between language learning anxiety and the support for female and male students even though Fisher’s Z transform did not confirm the significance of the differences. From the findings, it can be inferred that the students’ anxiety can be lowered to a certain extent by enhancing teacher and peer support in the cooperative learning environment so that students can be encouraged to enhance their confidence and self-esteem in language class.